UNGKAPAN MAKIAN DALAM BAHASA MINANGKABAU SOPIR ANGKOT DI KOTA PADANG - Wenni Yolanda; Dwi Mutia Chan; Yefrizon (Ekasakti Educational Scientific Journal, 2025)
Swearing expressions are a form of language used by society to express negative anger, annoyance or displeasure towards the person or party being addressed. Even though swearing is a negative use of language, many people find it difficult to get rid of the habit of using swear words. The aim of this research is to describe and explain the forms and types of swearing expression in Minangkabau language for public transportation drivers in the city of Padang. This research is a descriptive qualitative research describing the forms and types of swear nouns in Minangkabau language for public transportation drivers in Padang City. The instruments in this research were writing and recording equipment. The data in this research are words in the Minangkabau language in the form of expressions containing elements of swearing nouns used by public transportation drivers in the city of Padang. Data were collected using note-taking and recording techniques. The data source in this research is the source of verbal abuse from public transportation drivers at the Pasar Raya Terminal in Padang City. The results of this research show that in terms of nouns in swearing expressions, many public transportation drivers in Padang City still use swearing nouns that are not appropriate to their speech partners and there are still many public transportation drivers who speak using swearing expressions. The form of swear noun that is often used is a swear noun in the form of the word kanciang. The type of swear noun that is often used is a swear noun using the animal name dog.